Nourishing care for early child development in Eastern Mediterranean region through early child nutrition: A case studies from six countries - Al-Jawaldeh, Ayoub; Abul-Fadl, Azza; Al-Jawaldeh, Fuad Eid (Indian Journal of Child Health, 2020)
Background: An optimum brain development requires a stimulating environment, adequate nutrients, and social interaction but is challenged by poverty and illiteracy. Aim: This study aims to assess the status of early child education (ECE) and child development (ECD) in relation to early feeding practices. Materials and Methods: The global data for ECE and ECD were obtained from the demographic health surveys. Breastfeeding practices, early intake of iron, and Vitamin A through foods versus supplements were studied in relation to ECE and ECD in the 31 provinces of six countries by socioeconomic status. ECE, stimulation, and care were studied for 16 countries in the region. Descriptive statistics and Pearson’s correlation were used for analysis with a cutoff of p